Developing an Interactive English Teaching Module for Fashion Students at Grade X SMKN 1 Mataram by Using Quizizz Application - Riyadussolihatil, Ulumi; Sujana, I Made; Apgrianto, Kurniawan; Melani, Boniesta Zulandha; Alfin Haris Munandar, La Ode (Kirana Publisher (KNPub), 2025)
Vocational high school students need to learn the English language tailored to their specific majors. It is necessary to design the specific module for their chosen field, especially in fashion majors. This study aimed to design an interactive English teaching module using Quizizz for a fashion major in a vocational high school, along with discovering the feasibility of the English teaching module in supporting teaching-learning in English for fashion majors. This is a Research and Development (R&D) study with the ADDIE model consisting of five phases: analysis, design, development, implementation, and evaluation. Interviews, documentation, and expert validation questionnaires were used to collect the data. The data were analyzed using quantitative and qualitative analysis. The developed English teaching module using Quizizz resulted in three sections: introduction, main lessons, and assessments with different variations of feature tasks such as slides, poll, multiple-choice, fill-in-the-blanks, match, reorder, drag-drop and drop-down, draw, audio responses, and open-ended enriched the interactivity of the module. The results of expert validation for the module showed high feasibility for the module to use in the classroom, with an average percentage score of 96% for content and 94% for media. Based on the result, it can be shown that the English teaching module using the Quizizz application is very good to be applied in English teaching and learning for fashion majors.